Problems and Solutions for The Development of Sustainable Cash Waqf Linked Sukuk (CWLS) - Afifah, Rana Catleya Ega; Iqbal, Muhammad (IQTISHADIA, 2022)
The purpose of the research is to identify the problems that exist in the implementation of the Cash Waqf Linked Sukuk (CWLS) program as well as alternative solutions for sustainable development. This study uses a qualitative approach with the Analytic Network Process (ANP) method through literature studies, in-depth interviews, and giving questionnaires to regulators, practitioners, and academics related to the CWLS program. Based on the results from several sources, it was found that the problems arising from the CWLS program were grouped into three important aspects: collection, management, and reporting. The main problems that are of concern to the aspect of the gathering are institutional capacity, community knowledge, and community literacy and education. In the management aspect, the main problem lies in the knowledge of Nazhir and the capacity of professional Nazhir human resources. While the reporting aspect is the use of information technology which is the main problem. The research results obtained five solutions for developing CWLS to run sustainably. Of the five strategies offered between one another, none is more dominant. Therefore, the five strategies need to be implemented simultaneously to achieve a sustainable CWLS program.